2016
DOI: 10.4103/0253-7613.174528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orexin A antagonist (SB-334867) infusion into the nucleus accumbens on consummatory behavior and alcohol preference in Wistar rats

Abstract: Objective:Nucleus accumbens (NAcc) has a role in addiction and ingestive behavior. In order to assess orexinergic system involved in this, we infused Orexin A antagonist and assessed the effect on food intake fluid intake and alcohol preference in Wistar rats.Materials and Methods:Inbred Wistar rats (n = 54) were divided into control and experimental groups (low dose and high dose). Using stereotaxic method, guide cannula was set in place bilaterally to reach NAcc. Low dose (3 ng) and high dose (6 ng) of Orexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The role of Hcrt neurons in promoting reward seeking behaviors and cue-induced reinstatement has been established for a variety of drugs of abuse including cocaine (Borgland, Taha, Sarti, Fields, & Bonci, 2006; Boutrel et al, 2005; Harris, Wimmer, & Aston-Jones, 2005; Smith, See, & Aston-Jones, 2009; Smith, Tahsili-Fahadan, & Aston-Jones, 2010), ethanol (Mayannavar, Rashmi, Rao, Yadav, & Ganaraja, 2014, 2016; Shoblock et al, 2011; Srinivasan et al, 2012), nicotine (Dehkordi et al, 2017; Hollander, Lu, Cameron, Kamenecka, & Kenny, 2008; LeSage, Perry, Kotz, Shelley, & Corrigall, 2010; Plaza-Zabala, Martin-Garcia, de Lecea, Maldonado, & Berrendero, 2010), morphine (Georgescu et al, 2003; Harris et al, 2005; Harris, Wimmer, Randall-Thompson, & Aston-Jones, 2007; Narita et al, 2006; Sharf, Guarnieri, Taylor, & DiLeone, 2010; Sharf, Sarhan, & Dileone, 2008; Zarepour, Fatahi, Sarihi, & Haghparast, 2014), and heroin (Smith & Aston-Jones, 2012). These effects are thought to be mediated by direct projections to both components of the mesolimbic reward circuit, the ventral tegmental area (VTA) (Baimel & Borgland, 2015; Borgland, Storm, & Bonci, 2008; Borgland et al, 2006; España, Melchior, Roberts, & Jones, 2011; España et al, 2010; Hrabovszky et al, 2013; Muschamp et al, 2014; Srinivasan et al, 2012; Taslimi et al, 2012; Zarepour et al, 2014) and the nucleus accumbens (NAc) (Mayannavar et al, 2014, 2016; Mori, Kim, & Sasaki, 2011; Mukai et al, 2009; Sharf et al, 2008; Thorpe & Kotz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Hcrt neurons in promoting reward seeking behaviors and cue-induced reinstatement has been established for a variety of drugs of abuse including cocaine (Borgland, Taha, Sarti, Fields, & Bonci, 2006; Boutrel et al, 2005; Harris, Wimmer, & Aston-Jones, 2005; Smith, See, & Aston-Jones, 2009; Smith, Tahsili-Fahadan, & Aston-Jones, 2010), ethanol (Mayannavar, Rashmi, Rao, Yadav, & Ganaraja, 2014, 2016; Shoblock et al, 2011; Srinivasan et al, 2012), nicotine (Dehkordi et al, 2017; Hollander, Lu, Cameron, Kamenecka, & Kenny, 2008; LeSage, Perry, Kotz, Shelley, & Corrigall, 2010; Plaza-Zabala, Martin-Garcia, de Lecea, Maldonado, & Berrendero, 2010), morphine (Georgescu et al, 2003; Harris et al, 2005; Harris, Wimmer, Randall-Thompson, & Aston-Jones, 2007; Narita et al, 2006; Sharf, Guarnieri, Taylor, & DiLeone, 2010; Sharf, Sarhan, & Dileone, 2008; Zarepour, Fatahi, Sarihi, & Haghparast, 2014), and heroin (Smith & Aston-Jones, 2012). These effects are thought to be mediated by direct projections to both components of the mesolimbic reward circuit, the ventral tegmental area (VTA) (Baimel & Borgland, 2015; Borgland, Storm, & Bonci, 2008; Borgland et al, 2006; España, Melchior, Roberts, & Jones, 2011; España et al, 2010; Hrabovszky et al, 2013; Muschamp et al, 2014; Srinivasan et al, 2012; Taslimi et al, 2012; Zarepour et al, 2014) and the nucleus accumbens (NAc) (Mayannavar et al, 2014, 2016; Mori, Kim, & Sasaki, 2011; Mukai et al, 2009; Sharf et al, 2008; Thorpe & Kotz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The current study demonstrates that motivation for food (as indicated by lever response rates) occurs outside of the SNc, in a circuit independent of that which regulates habitual actions. Prior studies show that SB-334867 administered into the nucleus accumbens or ventral tegmental area reduces food intake [ 44 , 67 , 75 ], making the ventral, rather than dorsal, striatal circuit a possible site for these effects when SB-334867 was systemically administered in the current study [ 3 ].…”
Section: Discussionmentioning
confidence: 96%
“… 36,178 Orexin‐B, which predominantly stimulates OX2‐R, has only minor response on feeding, supporting the key role of OX1‐R in these physiological processes. Indeed, under various conditions, the selective blockade of OX1‐R with the 1‐SORA SB‐334867 inhibits consummatory behavior, after IP at high dose 31,184 or central injections 185,186 . SB‐334867 , however, is not fully devoid of off‐target effects, thus experiments with this compound have to be regarded with caution 187,188 .…”
Section: Pharmacological Potential Of Dual or Subtype‐selective Ox‐r ...mentioning
confidence: 99%
“…Indeed, under various conditions, the selective blockade of OX1-R with the 1-SORA SB-334867 inhibits consummatory behavior, after IP at high dose 31,184 or central injections. 185,186 SB-334867, however, is not fully devoid of off-target effects, thus experiments with this compound have to be regarded with caution. 187,188 The identification of many other physiological responses connected with the orexinergic signaling, including motivation to obtain food and reward-related factors, like palatable food, prompted the investigation of the role of OX-Rs in compulsive and dysregulated eating behaviors, such as binge-eating.…”
Section: Eating Disordersmentioning
confidence: 99%